Pengaruh Pemahaman Wakaf Terhadap Niat Berwakaf Tunai Jama’ah Masjid di Kecamatan Kota Ponorogo - Abdul Latif Latif; Imam Haryadi Haryadi; Adib Susilo Susilo (Islamic Economics Journal, 2021)
This research aimed to seek the influence of waqf understanding on cash waqf intention of the mosque congregation at the District of Ponorogo. The method employed in this study is multiple regressions with primary data collected from 150 respondents of 5 big mosques in the District of Ponorogo within the questionnaire. The result of the study shows that all variables of waqf understanding namely basic understanding of waqf, understanding of waqf benefit, and understanding of waqf laws are simultaneously influenced the dependent variable with significant impact. Meanwhile, partially understanding the benefit of waqf positively significant influenced the intention to participate and donate cash waqf, while the rest variables had no impact on the intention to participate and donate cash waqf.